On the Question of African “Protest Identity” - Kharitonova Elena Vladimirovna (Ученые записки Института Африки Российской академии наук)
The article presents an analytical review of approaches to the emergence of African protest identity. It examines the causes and forms of protest identity in Africa, both historically and in the present. The African protest identity is associated with colonial cultural pressure and constitutes a reaction to the discrediting of African culture and the personality of an African. Two opposing approaches to colonization are highlighted in the research. The Eurocentric approach considers colonization to be a beneficial, civilizing project, whereas Africans themselves see it as a tragedy that led to an identity crisis and the construction of new forms of identity (E. Blyden, “The Negritude” by L.S. Senghor).